Design and Validation of a Social Banking Model Based on Artificial Intelligence in Iranian Cooperative Banks - Khoshchehreh Mohammadi, Ramin; Hosseini Shakib, Mehrdad; Khoddam, Mahmood; Ramezani, Ali (Business, Marketing, and Finance Open, 2026)
In today's banking landscape, artificial intelligence (AI) is recognized as a key tool for transforming processes and enhancing banking services. However, the adoption of AI in cooperative banks, which are inherently social and customer-centric, still requires appropriate and practical modeling. This study aims to design and validate a social banking model leveraging AI functionalities in cooperative banks. The research is applied in nature and employs a mixed-method approach (qualitative-quantitative). In the qualitative phase, thematic analysis was conducted on 298 scientific articles published between 2014 and 2024, identifying the dimensions and components of the model. In the quantitative phase, the extracted model was validated through confirmatory factor analysis (CFA) and surveys with 82 banking industry experts. The findings revealed that the final model consists of nine dimensions and 54 components, with "AI technology and infrastructure," "legal and regulatory aspects," and "risk and security" being the most influential factors for the model's success. Additionally, the analysis demonstrated that the proposed model exhibits acceptable reliability and validity, explaining 88% of the variance in the dependent variable. The results suggest that implementing AI in cooperative banks can not only improve operational performance but also contribute to sustainable development and enhance their social responsibility. It is recommended that cooperative banks invest in technological infrastructure and address legal and security requirements to take practical steps toward implementing this model.